The Method of Ilman Wa Ruhan in Strengthening The Learning Outcomes of Tahsin Tahfidz Al-Qur'an at SMP IT Al-Qudwah Musi Rawas - Wafa, Ali; Khozin, Khozin; Hakim, Rahmad (West Science Interdisciplinary Studies, 2025)
This research aims to analyze the implementation of the Ilman Wa Ruhan Method in Strengthening the Learning Outcomes of Tahsin Tahfidz Al-Qur'an at SMPIT Al-Qudwah Musi Rawas. This research uses a qualitative approach with a case study type of research. The research location is located at SMPIT Al-Qudwah Musi Rawas South Sumatra. This research data was obtained through interviews, observation and documentation. Data analysis used in this research is based on the analysis theory of Miles, Hubberman and Saldana, namely: data collection, data condensation, data presentation and conclusion drawing. The results showed that the implementation of the Ilman Wa Ruhan method at SMPIT Al-Qudwah Musi Rawas was carried out thoroughly through three main stages: careful planning with the preparation of lesson plans according to JSIT standards, the implementation of learning which included adab, tahsin, and tahfidz material with an interactive and gradual approach, and evaluation carried out formatively and summatively. The Ilman Wa Ruhan method is proven to be effective in strengthening the learning outcomes of tahsin tahfidz al-Qur'an because it is able to form students who are not only fluent in reading and memorization, but also have good manners and spiritual understanding of the Qur'an.